HEALTH PROMOTION TOURISM INNOVATION IN WORLD HERITAGE CITIES FOR THE ELDERLY IN INDUSTRIAL ZONES PHRA NAKHON SI AYUTTHAYA PROVINCE - Pramann, Prawit; Pramann, Saowaluk; Akkarapatkamchai, Phawat (Journal of Social Science and Cultural, 2024)
This research aims to synthesize competencies for promoting holistic health. To develop health-promoting tourism innovations in world heritage cities, and to convey the use of innovative health promotion tourism in the World Heritage City for the elderly in industrial areas, Phra Nakhon Si Ayutthaya Province which conducts mixed methods research By using the results of quantitative studies to support the results of qualitative data through the process of the PDCA cycle, that is, Plan, Do, Check, and Act. The sample group consisted of 395 people. The research instrument was a holistic health promotion competency questionnaire and project lesson transcripts and semi-structured in-depth interviews with stakeholder groups. The content reliability was equal to 0.85, 1.00, and 1.00, respectively. Statistical analysis was performed using mean and standard deviation and content analysis. The research results found that: 1) Competency in promoting holistic health was found to have 4 aspects: planning, organization. operations and control, which are outstanding in terms of activities, places, and tourist attractions Culture and way of life of the people of Bang Pa-in District By working to promote holistic health for the elderly. The overall level was at a high level, with an average of 3.56, and the level of competency in health promotion tourism of World Heritage cities for the elderly was found to be at a low level overall, with an average of 3.22. 2) Innovation as a community tourism guide, The average value of appropriateness was 4.08, which was at a high level and feasibility was equal to 4.17 at a high level and 3) satisfaction with the community tourism guide Overall, it was at a high level with an average of 3.98.